Hereditary Diffuse Infiltrating Retinoblastoma. (2nd January 2016) - Schedler, Katharina J. E.; Traine, Peter G.; Lohmann, Dietmar R.; Haritoglou, Christos; Metz, Klaus A.; Rodrigues, Eduardo B.
Abstract: Retinoblastoma is one of the most common childhood cancers. The diffuse infiltrating retinoblastoma is a rare subtype of this neoplasm. The majority of cases of diffuse infiltrating retinoblastoma are unilateral and occur sporadically. Herein we report on a family with three children affected by retinoblastoma, among them one girl with diffuse infiltrating retinoblastoma. This girl was diagnosed at the age of 8 years with a unilateral diffuse infiltrating retinoblastoma. By contrast, the two brothers became clinically apparent in the first 2 years of life with bilateral retinoblastoma. The parents were clinically unremarkable. Genetic analysis of RB1 gene was performed. The girl with diffuse infiltrating RB was found to be heterozygous for an oncogenic mutation in the RB1 gene that was also carried by both brothers and the father of the family. These results show that diffuse infiltrating retinoblastoma can develop on the background of a hereditary predisposition to retinoblastoma.